Research and Development Spillovers Impact on Productivity (Case study: Iran's agricultural sector) - Seyedsafdar Hoseyni; Habib Shahbazi; Akram Abasifar (مدیریت بهره وری, 2015)
Research and development (R&D) is a suitable strategy for increasing agricultural production and supply and alleviating poverty and food shortages. Research and development affects agricultural productivity and production in several ways. Spillovers of research and development from other sectors and foreign countries has an important role in increasing agricultural productivity. In this study, by using OLS and Almon distribution lag model, agricultural research and development policy and spillovers for the years 1959-2012 are evaluated .The results indicate that agricultural research and development elasticity is 0.311, other sectors research and development elasticity is 0.109, capital input import elasticity is 0.057 and intermediate input import is 0.046. So, supply of agricultural research and development parameter is 0.193, supply of other sectors research and development parameter is 0.068, supply of imported research and development (capital input) parameter is 0.035 and supply of imported (intermediate input) research and development parameter is 0.029.Therefore, agricultural research has more impact than other sectors research (spillovers) on agricultural productivity.